Growth, Yield and Yield Components of Lentil as Influenced by Irrigation and Weeding Regime (Journal of Environmental Science and Natural Resources, 2015)
The experiment was carried out to study the effect of irrigation and weeding regime on growth, yield and yield contributing characters of lentil. The experiment was laid out in a split-split plot design with three replications. Four levels of irrigation viz. control or no irrigation (I0), one irrigation (I1), two irrigation (I2) and three irrigations (I3) and three weeding regime viz. control weeding (W0), one weeding (W1) and two weedings (W2) were used. Irrigation had significant effect on all the growth, yield and yield contributing characters. The highest TDM , CGR and all the yield contributing characters like plant height, number of branches plant-1, number of pods plant-1, number of effective pods plant-1, number of seeds plant-1, number of filled seeds plant-1, 1000-seed weight and stover yield were obtained from three irrigations (I3) and consequently it produced the highest seed yield. Effect of weeding regime was significant in respect of on the growth, yield and yield contributing characters. All the yield contributing characters except non-effective pods plant-1 were found the best when two weedings were done and as a result it produced the highest seed yield. With some exception two weedings showed highest values of TDM, CGR and other growth character. Finally the results suggest that three irrigations with two weedings are better practices to get higher growth and yield of lentil.DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22225 J. Environ. Sci. & Natural Resources, 7(2): 155-161 2014